Tax Morale and the Role of Social Norms and Reciprocity: Evidence from a Randomized Survey Experiment - Philipp Doerrenberg; Andreas Peichl (Institute of Labor Economics (IZA), 2018)
We present the first randomized survey experiment in the context of tax compliance to assess the role of social norms and reciprocity for intrinsic tax morale. We find that participants in a social-norm treatment have lower tax morale relative to a control group while participants in a reciprocity treatment have significantly higher tax morale than those in the social-norm group. This suggests that a potential backfire effect of social norms is outweighed if the consequences of violating the social norm are made salient. We further document the anatomy of intrinsic motivations for tax compliance and present first evidence that previously found gender effects in tax morale are not driven by differences in risk preferences.
Keywords: H20; H32; H50; C93; 330; tax compliance; tax evasion; intrinsic motivations; tax morale; social norms; reciprocity